Femur development in fetal growth restriction as observed on prenatal magnetic resonance imaging. (2nd May 2023) - Nemec, S. F.; Schwarz‐Nemec, U.; Prayer, D.; Weber, M.; Bettelheim, D.; Kasprian, G.
ABSTRACT: Objective: To investigate human femur development in fetal growth restriction (FGR) by analyzing femur morphometrics and distal epimetaphyseal features on prenatal magnetic resonance imaging (MRI). Methods: This was a retrospective study of 111 fetuses (mean gestational age (GA), 27 + 2 weeks (range, 19–35 weeks)) with FGR associated with placental insufficiency without other major abnormalities and 111 GA‐matched normal controls. On 1.5‐Tesla echoplanar MRI, femur morphometrics, including diaphyseal length, epiphyseal length and epiphyseal width, were assessed. Using a previously reported grading system, epimetaphyseal features, including cartilaginous epiphyseal shape, metaphyseal shape and epiphyseal ossification, were analyzed qualitatively. To compare FGR cases and controls, the paired t ‐test was used to assess morphometrics, generalized estimating equations were used for epimetaphyseal features and time‐to‐event analysis was used to assess the visibility of epiphyseal ossification. Results: There were significant differences in femur morphometrics between FGR cases and controls (all parameters, P < 0.001), with bone shortening observed in FGR. No significant differences were found in the distribution of epimetaphyseal features between FGR cases and controls (epiphyseal shape, P = 0.341; metaphyseal shape, P = 0.782; epiphyseal ossification, P = 0.85). Epiphyseal ossification was visible at a median of 33.6 weeks in FGR cases and at 32.1 weeks in controls ( P = 0.008). Conclusions: On prenatal MRI, cases with FGR associated with placental insufficiency exhibit diaphyseal and epiphyseal shortening of the femur. However, FGR cases and normal controls share similarly graded distal epimetaphyseal features. Consequently, these features may not be appropriate MRI characteristics for the identification of FGR. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.